ANALISIS PENGELOLAAN KEUANGAN DESA DI DESA RANTAU BARU KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Nur M Alfa Zikri; Nurman Nurman (UIR Press, 2018)
The research aims to determine the level of rural finance management of Rantau Baru Subdistrict PangkalanKerinci District of Pelalawan. The assessmentindicators used include of acceptance administration , expenses administration and financial accountability. Type of research is located in the rural office of Rantau Baru Subdistrict PangkalanKerinci District of Pelalawan. This is a descriptive survey thattakes questionnaire priority as datas collectionand it can be used to analyze the empirical condition objectivity in the locationof the research.The populations of the research consists of 17 employees. The sampling technique that used in determining the individual sample is census techniques for employees. Techniques to collect the datas consist of used consist of primary data, collected by questionnaire techniques, interviews and secondary data collected using observation. While the data analysis technique used is to use a frequency table. Based on this analysis technique researchers assess and conclude that Analysis Financial Management of Rantau BaruSubdistrict Pangkalan Kerinci District of Pelalawan is in the interval good quite assessment. Recommendations to be considered especially with respecting to the recording of all revenues and expenditures in apbdes to be more attention to improve the effectiveness of the rural financial management.